(Auto)biographic narrative research and project workshops: a artisanship of life and formation in pandemic context (Praxis Educativa, 2024)
The pandemic context that began suddenly brought us, along with new ways of living, educational challenges to be faced in an unequal society governed by control. This article brings the experience of an extension course inspired by Delory-Momberger's biographical project studio, aligned with the (Auto)Biographical Narrative Research-training approach, carried out with a group of basic education teachers from public schools, mostly from Rio de Janeiro state. The proposal consisted of creating a conversation space for the artisanal production of research projects, presenting as a starting point the construction of narratives, oral and written, about the life history and training of the participants, through rescue and reflection of experiences as teachers in this specific period of pandemic. Based on this awareness, in a reflective movement, the teachers raised questions related to future academic projects.
Keywords: Narrative (auto)biographical research-formation; Project Workshop; Pandemic; Teaching; School